'(Although) it's not rocket science': a theoretical concept for assessing national space policies in Europe - Hansel, Mischa (2007)
Abstract: "This paper aims to contribute both to the establishment of theoretical tools for describing and explaining the evolution of national space policy as well as to the empirical analysis of changing national and multinational security space capabilities in Europe. The theoretical framework proposed below rests on a differentiation of five ideal-type levels of state disposal of technology, indicating a state's position in the order of space powers. These levels of control are utilisation, participation, cooperation, autonomy, and monopoly. The relevance of these levels of control lies in the corresponding distribution of distinct costs (political, socioeconomic and symbolic) and their domestic and/or international repercussions. Variations in national investment and activity across military and dual-use space technologies are caused by three types of variables: 1) the availability and attractiveness of utilisation, participation and cooperation options, 2) the amount of political, soci